The World Of Physics - "Avison, John" (Thomas Nelson and Sons: UK, 1989)
A clear and easy to follow textbook including material on forces, machines, motion, properties of matter, electronics and energy, problem-solving investigations and practice in experimental design.
Keywords: Physics - Textbook